PENGARUH KEMAMPUAN SDM, MOTIVASI TERHADAPKINERJA KARYAWAN DANREWARD SEBAGAI VARIABEL MODERATING Studi Kasus PT. Radio Suara Akbar Dan Radio Nada di Kabupaten Jember - Deni Budiman; Purnamie Titisari; Moehammad Fathorazzi (RELASI : JURNAL EKONOMI, 2016)
This study aims to determine the effect of human resources capabilities, motivation on employee performance and reward as moderating variable in the case studies Akbar Radio and Radio Nada Jember. This type of research is explanatory hypotheses are tested to determine whether there is influence of variable human resources capabilities, motivation, on employee performance and reward as moderating variable. In this study, the techniques used in probability sampling is purposive sampling, ie sampling techniques are taken on the basis of specific intent or purpose. Samples from this study are employees working in PT Radio Voice Tone FM Radio Akbar and some 42 employees. The results obtained are the link between the human resources capacity, motivation on employee performance and reward as moderating variable. Besides, there are also differences in the effect of applying reward Akbar Radio and Radio tone that did not apply the reward.